Placing the 2020 Belarusian Protests in Historical Context: Political Attitudes and Participation during Lukashenko’s Presidency - Hansen Michael A.; Ford Nicolè M. (Cambridge University Press, 2025)
In the wake of the most recent protests in Belarus following the 2020 Presidential Election, it is useful to explore patterns of satisfaction with the political system, confidence in political institutions, and political participation at different points in time during President Lukashenko’s rule. We utilize Wave 3 of the World Values Study (WVS) and Wave 7 of the Joint European Values Study (EVS)/WVS to (1) analyze whether citizens’ dissatisfaction with the Belarusian government differed between 1996 and 2018, and (2) whether there was a change in political participation during that period. Responses over time suggest that satisfaction with the government and confidence in institutions was not lower in 2018 than it had been in 1996. However, as we discuss in the article, this may be an artifact of authoritarian consolidation and concern/fears about revealing preferences. We also find that the willingness to engage in protests remained more or less the same between these two time periods, especially among those dissatisfied with the political system. These results suggest that once highly dissatisfied citizens took to the streets in 2020, a number of internal and external factors might have triggered a bandwagon effect that pushed other citizens to also join the demonstrations.